Hubungan Paparan Asap Rokok dengan Otitis Media Supuratif Kronik di RSUD Dr. Moewardi - Dian Nastiti Dwi Mahanani; Hadi Sudrajad; Hartono . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: The association between exposure to cigarette smoke with chronic suppurative otitis media is still debated. Cigarette smoke reduce the function of cilia, resulting blockage of mucus in the Eustachian tube. Besides of that, cigarette smoke is also a stressor that can lead to decreased immune system. This situasion make organism easier to develop and entry into the middle ear. This study aimed to determine the association between exposure to cigarette smoke with chronic suppurative otitis media in RSUD Dr. Moewardi. Methods: This study was observational by using case control design. Research subjects are grouped into case and control groups. The sample was selected by purposive sampling with inclusion and exclusion criteria have been determined. Data is collected by questionnaire of smoking history and medical record data of patients. Data were analyzed using Chi Square test with SPSS 17.0 for Windows. Results: There was a significant association between exposure to cigarette smoke with chronic suppurative otitis media in RSUD Dr. Moewardi. Samples with a history of smoking had a risk of chronic suppurative otitis media 4, 5 times higher than without a history of smoking (p = 0, 028; OR = 4, 5). Conclusions: There is a association between exposure to cigarette smoke with chronic suppurative otitis media in RSUD Dr. Moewardi. Smoking cigarette can increase the risk of chronic suppurative otitis media. Keywords: exposure to cigarette smoke, Chronic suppurative otitis media.